ChemInform Abstract: Recent Advances in the Discovery of N‐Myristoyltransferase Inhibitors. Issue 3 (January 2015) - Zhao, Can; Ma, Shutao
Abstract Review: [with particular focus on their activities, structure—activity relationships, and mechanisms; 74 refs.